Pengenalan Media Pembelajaran untuk Meningkatkan Hasil Belajar Siswa di SD - Primanita Sholihah Rosmana; Sofyan Iskandar; Nur Fitri Halimah; RIfa Aminah Salsabila; Rina Rohimah (Departement of Mathematics Education, 2023)
Learning media is a tool that can be used by a teacher to teach students about important and difficult subjects in various forms. This article aims to provide an overview of media coverage intended to provide information about the success of elementary school (SD) students. This study uses a quantitative approach using analytical techniques validation techniques and trials using standard gain techniques related to the use of instructional media. Data collection was collected through post-tests and pre-tests which were carried out on students with discussions that used the results of observations from several sources. The results showed that the post-test scores were better than the pre-test scores, this increase in learning outcomes was also in line with research that had been conducted by researchers who showed a standard gain value of 30.5. It can be concluded that there is an increase in student learning outcomes at the elementary level.